A Simplified Method for Obtaining cDNA of Low-Copy and Silent Eukaryotic Genes Using Human Renalase as an the Example - Fedchenko, V.I.; Kaloshin, A.A. (Biomedical Chemistry: Research and Methods, 2019)
A simplified «exon» method was developed for producing cDNA of low-copy and silent eukaryotic genes. It is based on assembly of the target gene from genomic DNA by direct synthesis of its exons, followed by their PCR-based joining without further purification of the amplicons. During the synthesis of exons, direct primers were used; these included about 20 nucleotides of the 3`-terminal sequence previous (from the amplified) exon and 20 nucleotides of the 5`-initial sequence of the amplified exon. Reverse primers included 20 nucleotides complementary to the terminal sequence of the amplified exon. Forward and reverse primers flanking the gene to be assembled included the restriction sites necessary for insertion into the expression vector. Using this approach it is possible to assemble almost any eukaryotic gene with a known nucleotide sequence of genomic DNA available in the database.